Circulation d’un modèle urbain "alternatif" ? - Nicolas Douay; Maryvonne Prévot (EchoGéo)
Tactical planning provides every citizen to act materially on its everyday and immediate urban environment and to make it more pleasant, without waiting for the authorities / stakeholders responsible for planning and urbanism to answer his aspirations. At first glance it calls into question the central role of public institutions in the regulation and control of the public space and amenities. In this sense, the societal conditions of the emergence of these new initiatives of citizen ownership of public spaces, abandoned or not, must be analyzed. If the tactical planning endeavors to show that everyone has the capacity to transform, at the local level, how to think and plan the city, not as in his own name but on behalf of interest shared by other members of his community, alternative urban model relies thus on a large community connected to social networks that allow the movement to adopt new practices and initiatives and to adapt it in different local contexts. The tactical urbanism carries the standard of disinterested exchanges and values ​​promoted by the pioneers of the digital vector of an active democracy or it is only the new faces of a mainstream solutions in urban planning? Finally we can question the transgressive and alternative characters because it seems to have been established as one of the aspects of conventional urban design solutions? The case of Paris illustrates the reception of the model and its gradual institutionalization.